Supporting Clinical Mental Health Counseling Doctoral Supervisors in Supervising School Counselors-in-Training: Challenges and Strategies for Integration - Yu-Hsun Peng; Derron Hilts; Yanhong Liu (Teaching and Supervision in Counseling, 2024)
This conceptual article underscores the critical need for tailored supervision for school counselors-in-training (SCITs), emphasizing challenges arising from differences in training, role ambiguity, and limited understanding of pK-12 educational contexts when overseen by doctoral supervisors with clinical mental health counseling (CMHC) backgrounds. We advocate for enhanced training and support for doctoral students from CMHC backgrounds to more effectively supervise SCITs. Bridging the gap between SCITs and counselor education doctoral training, we emphasize adjustments to supervision training and implications for the supervision of school counselor trainees.
Keywords: school counseling supervision; school counselors-in-training (SCITs); clinical mental health; counselor education doctoral students